Análise para o domínio “Cognição” do protocolo Individualized Music Therapy Assessment Profile (IMTAP) - Alexandra Monticeli de Souza Ricardo Belato (2020)
Music therapy has been increasingly consolidated as a science, however, still young, having emerged after the Second World War (Oliveira & Gomes, 2014). A large part of its assessment instruments, therefore, still need to be proven effective in order to be able to plan interventions in line with the individual's needs. Therefore, we investigated the relationship between a set of music therapy activities that test the cognitive functions included in the “Cognition” domain of the Individualized Music Therapy Assessment Profile (IMTAP) protocol with a battery formed by the psychological instruments normally used in a cognitive assessment of reading. Next, based on the relationships inferred between musical language and written language and studies on musical intervention in dyslexia, the possibility that children identified at risk of dyslexia could have some impairment in the IMTAP “Cognition” domain was explored. The sample included 30 second year students from a public school in the region of Pampulha in the city of Belo Horizonte, aged between 7 and 8 years old, who were submitted to the aforementioned music therapy activities (created for this dissertation based on the domain reference IMTAP “Cognition” and four techniques proposed by the Neurological Music Therapy approach) and the battery of psychological tests (Raven Progressive Matrices; WISC Digits subtest; Psychological Attention Battery, Pseudoword Repeat Test for Brazilian Children; Naming Speed and Test Reading Comprehension). The expectations of the study have not been confirmed. Through Pearson's correlations that although significant, but very low, no relationship was found between music therapy activities and the battery of psychological tests, suggesting that the constructs evaluated by the IMTAP “Cognition” domain are different from the test constructs used for assess cognitive functions such as attention, memory and information sequencing. In the same direction, children at risk of dyslexia did not show any impairment in the musical skills of the same domain. Finally, when evaluating the possible flaws in the construction of the applied music therapy activities, instructions for the construction of new paths were built with the intention of assisting in future research.